2023
DOI: 10.3390/foods12234318
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of CCSER1 Gene and Their Correlation with Milk Quality Traits in Gannan Yak (Bos grunniens)

Guowu Yang,
Juanxiang Zhang,
Xiaoyong Ma
et al.

Abstract: Coiled-coil serine-rich protein 1 (CCSER 1) gene is a regulatory protein gene. This gene has been reported to be associated with various economic traits in large mammals in recent years. The aim of this study was to investigate the association between CCSER1 gene single nucleotide polymorphisms (SNPs) and Gannan yaks and to identify potential molecular marker loci for breeding milk quality in Gannan yaks. We genotyped 172 Gannan yaks using Illumina Yak cGPS 7K liquid microarrays and analyzed the correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Ear tissue samples were collected from 172 Gannan yaks and stored in liquid nitrogen before being transported back to the laboratory for storage at −80 °C. DNA was extracted from the ear tissue samples following the instructions of the Magnetic Animal Tissue Genomic DNA Kit (DP341, Tiangen Biochemical Technology Co., Ltd., Beijing, China) [ 24 ]. The extracted samples were left to stand on a magnetic rack for 2 min, and after the magnetic beads were completely adsorbed, the DNA solution was transferred to a new centrifuge tube and stored under appropriate conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Ear tissue samples were collected from 172 Gannan yaks and stored in liquid nitrogen before being transported back to the laboratory for storage at −80 °C. DNA was extracted from the ear tissue samples following the instructions of the Magnetic Animal Tissue Genomic DNA Kit (DP341, Tiangen Biochemical Technology Co., Ltd., Beijing, China) [ 24 ]. The extracted samples were left to stand on a magnetic rack for 2 min, and after the magnetic beads were completely adsorbed, the DNA solution was transferred to a new centrifuge tube and stored under appropriate conditions.…”
Section: Methodsmentioning
confidence: 99%
“…In the yak, PRKD1 gene is located on chromosome 17, and the correlation between PRKD1 gene polymorphism and milk quality in yak has not been mentioned. Previously, we found that three SNPS in the CCSER1 gene were associated with milk quality (milk fat, protein, and casein) in Gannan yaks [ 19 ]. Regions reported to affect milk quality traits in dairy cows are concentrated on chromosomes 1, 6, 11, 13, 14, and 18 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%